2017
DOI: 10.1039/c7ra06744e
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing perovskite film fluorescence by simultaneous near- and far-field effects of gold nanoparticles

Abstract: Gold nanoparticles are incorporated into PEDOT:PSS for enhanced perovskite fluorescence, which originates from simultaneous near- and far-field effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Ag nanofibers were introduced into PQD nanofiber membrane via layer-by-layer electrospinning method and Ag nanofibers of each layer interweaved with PQD nanofibers of the adjacent layer. We defined PQDs-layer/Ag NPs-layer/ PQDs-layer as an analytical periodic unit and proved that one unit possesses a ~4.8 folds fluorescence enhancement, which is a significant improvement compared with ~1.7 folds fluorescence enhancement for CsPbBr 3 QDs and ~4.0 folds fluorescence enhancement for MAPbBr 3 QDs reported elsewhere [23,26]. Furthermore, we interpreted the plasmonic enhancement mechanism of this system by simulating the light field distribution of Ag nanofibers.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…Ag nanofibers were introduced into PQD nanofiber membrane via layer-by-layer electrospinning method and Ag nanofibers of each layer interweaved with PQD nanofibers of the adjacent layer. We defined PQDs-layer/Ag NPs-layer/ PQDs-layer as an analytical periodic unit and proved that one unit possesses a ~4.8 folds fluorescence enhancement, which is a significant improvement compared with ~1.7 folds fluorescence enhancement for CsPbBr 3 QDs and ~4.0 folds fluorescence enhancement for MAPbBr 3 QDs reported elsewhere [23,26]. Furthermore, we interpreted the plasmonic enhancement mechanism of this system by simulating the light field distribution of Ag nanofibers.…”
Section: Introductionmentioning
confidence: 73%
“…In the proposed structure (Figure 5a), the polymers (PVDF and PVP) that are highly transparent in the emission range of MAPbBr 3−x Cl x QDs separate the emitters from Ag NPs at an appropriate distance, and therefore eliminate the fluorescence quenching. According to TEM measurements of PVDF-PQDs nanofibers and PVP-Ag nanofibers, the average nearest distance between PQDs and Ag NPs can be deduced to be 7 nm, which is within the near-field enhancement of plasmonic nanoparticles [26,36]. In addition to the near-field, it is reported that the far-field of plasmonic nanoparticles also contributes to the fluorescence enhancement [26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Perovskite synthesis methods: The MAPbBr 3 solution was prepared by dissolving MABr and PbBr 2 (MABr > 99.9%, PbBr 2 > 99.9%, 1.5:1 molar ratio, Xi'an Polymer Light Technology Corp., Xi'an, China) in DMF solution (reported in our previous research work [33,35]). Then chlorobenzene solution was dropped into the DMF solution until saturation, accelerating perovskite material crystallization.…”
Section: Methodsmentioning
confidence: 99%